The impact of globalization on the interpretation of regional growth and development - Jovović, Dušanka M. (Collection of Papers of the Faculty of Philosophy in Priština, 2015)
In the last decade of the twentieth century, there was a change of interpretation of regional growth and development, not only in economically developed countries but also countries in development. The previous, conventional (Keynesian and neoclassical) interpretations of regional growth and development began to give way to new explications, explanations based on the strengthening of enogenic potentials of the region. There is an agreement in theory that the phenomenon of globalization is a key factor in those changes.The new approach to the factors of economic growth and development focuses on improving competitiveness. The intensity of economic growth and the quality of economic development of a region is the result of internal forces, and the competence of the local development policy, and less the result of forces that act outside of it. This new interpretation of regional growth and development emphasizes the importance of networks and forces that drive innovation, and the process of creation and dissemination of knowledge. It changes the key assumptions of the Keynesian and neoclassical postulates of economic growth and development in regions and contribute to a better understanding of the regional reality in the era of globalization, as a kind of compression of time and space over the past twenty years.
Keywords: local capital; increasing taxes; growth; interpretation of regional economic growth and development; region; globalization